KARAKTER KUNCI PEMBEDA ANTARA ORANGUTAN KALIMANTAN (Pongo pygmaeus) DENGAN ORANGUTAN SUMATERA (Pongo abelii) - Prayogo, H. -; Thohari, A.M -; Sholihin, D.D -; Prasetyo, L.B -; Sugardjito - (Direktorat Sumber Daya Akademik dan Perpustakaan, 2014)
Orangutans are great apes left in Asia, at the time ofthe Asian mainland is a unity, orangutan has a fairlywide distribution in Asia, especially in Southeast Asia.In the event of an increase in sea levels, which had beenfused into Mainland fragmented into islands. Thisseparation into a barrier that restricts the movementof orangutans. Currently their range is limited onlyin Borneo and Sumatra. Long period separationwith different habitat conditions have an impact onthe orangutans. In morphology occurs a significantdifference between the orangutans of Borneo andSumatra, in addition to the utilization of molecularbiology technology has also been able to reveal thepresence of significant differences between thesetwo species, making it the orangutan then serve as adifferent species, namely Pongo pygmaeus on Borneoorangutans and P. abelii for Sumatran orangutans,even for orangutans in Borneo has been divided intothree sub species namely P. pygmaeus pygmaeus,P. p. morio and P. p. wurmbii. With the unfolding ofthe different species and these sub species, the useof molecular biology technology becomes integral inconservation action against this type primarily forrelocation or translocation of orangutans into the wild.Key words: Orangutan, Pongo pygmaeus, P. abelii, molecularbiology technology, conservation